Pancreatic Metastasis from Carcinoid Midgut Tumor. A Case Report - Moletta, Lucia; Milanetto, Anna Caterina; Alaggio, Rita; Sperti, Cosimo; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2013)
Context Metastatic lesions to the pancreas are rare. We present a case of an ileal carcinoid tumor with a synchronous pancreatic metastasis. Case report A 68-year-old male patient was admitted to our clinic in 2008 for diarrhea and flushing. Urinary serotonin (2x upper reference limit), 5HIAA (5x upper reference limit) and chromogranin A (2.5x upper reference limit) were increased. An octreoscan scintigraphy showed a focal uptake in the pancreatic head and a slight uptake in the lower abdomen. An abdominal CT scan did not show any pancreatic lesions, but a slightly enlarged pancreatic duct in the body of the pancreas. We reviewed the CT scan imaging and we found a hypervascular ileal lesion, confirmed by small bowel barium study. The pancreatic lesion was confirmed by MRI and resulted slightly hypermetabolic with 18FDG-PET (SUV of 2.15). In November 2008 the patient underwent a duodenum-preserving pancreatic head resection (DPPHR), a cholecystectomy, an ileal resection (about 80 cm) and ablation of small multiple peritoneal nodules. Histology showed multiple well differentiated (Ki67 <2%) ileal carcinoid tumors with lymph-node metastases and tiny peritoneal secondary lesions. The pancreatic lesion resulted to be a metastasis of the carcinoid with positive serotonin staining. The patient is still alive with diarrhea, biochemical evidence of disease and multiple pulmonary metastases 48 months after surgery. Conclusion Pancreas is an uncommon site of metastatic spread in midgut carcinoids and should be considered in case of pancreatic synchronous lesions. In the literature we found a single case report in the last 10 years.